The symptoms of modernization and its impact when the originals (Journal of the College of Basic Education, 2023)
The Sunnah is of great importance in knowing the Islamic rulings. It is considered with the Holy Quran The first source of Islamic legislation if it is clear or affirmative to it, and the second source if it isThe institution of a rule that the Holy Qur’an was silent about (1). It is well known among the specialists that working according to the purified Sunnah after the authoritative methods ofAccess to it and the authenticity of its significance depend on the absence of a stable contradiction between its texts (2); so It confuses the legal stance towards jurisprudential facts (3). Therefore, there is a stable discrepancy in